Outer membrane proteins analysis of Shigella sonnei and evaluation of their antigenicity in Shigella infected individuals - Harikrishnan, Hemavathy; Singh, Kirnpal Kaur Banga; Ismail, Asma (Public Library of Science (PLoS), 2017)
Bacillary dysentery caused by infection with Shigella spp. remains as serious and common health problem throughout the world. It is a highly multi drug resistant organism and rarely identified from the patient at the early stage of infection. S. sonnei is the most frequently isolated species causing shigellosis in industrialized countries. The antigenicity of outer membrane protein of this pathogen expressed during human infection has not been identified to date. We have studied the antigenic outer membrane proteins expressed by S. sonnei, with the aim of identifying presence of specific IgA and IgG in human serum against the candidate protein biomarkers. Three antigenic OMPs sized 33.3, 43.8 and 100.3 kDa were uniquely recognized by IgA and IgG from patients with S. sonnei infection, and did not cross-react with sera from patients with other types of infection. The antigenic proteome data generated in this study are a first for OMPs of S. sonnei, and they provide important insights of human immune responses. Furthermore, numerous prime candidate proteins were identified which will aid the development of new diagnostic tools for the detection of S. sonnei.